MENAKAR PERAN KINERJA PEMBIAYAAN SYARIAH DALAM MENINGKATKAN PROFITABILITAS BANK SYARIAH - Ahmad Haris; Ardiani Ika Sulistyawati; Aprih Santoso (Sekolah Tinggi Ilmu Ekonomi Semarang, 2020)
The research objective was to prove the effect of mudharabah financing, musyarakah financing and ijarah financing on the profitability (ROA) of Bank Muamalat Indonesia. The research object is Bank Muamalat Indonesia which is a Sharia Commercial Bank (BUS). Bank Muamalat Indonesia data is in the form of quarterly financial reports for the 2012-2019 period, so there are 32 sample data. This study uses secondary data with documentation methods. Data analysis used the classical assumption test (normality / Kolmogorov-Smirnov test, multicollinearity test, heteroscedasticity test, autocorrelation test - Durbin-Watson); Hypothesis testing (t and F tests) and coefficient of determination (R2) as well as multiple linear regression analysis. The results of the study are mudharabah and ijarah financing have no effect on the profitability (ROA) of Bank Muamalat Indonesia, meanwhile, musharaka financing has a negative effect on the profitability (ROA) of Bank Muamalat Indonesia in 2012-2019